The use of bolted side aluminum alloy plates for flexural capacity of reinforced concrete beams: An experimental investigation. (August 2022) - Zhang, Zhi; Liu, Yue-ting; Li, Ling-zhi; Lu, Zhou-dao
Abstract: Bolted side-plating (BSP) is an effective retrofitting technique that enhances reinforced concrete (RC) beams by anchoring steel plates onto the beam's two opposite side faces with bolt connection. Compared to steel plates, aluminum alloy plates have advantages such as a greater strength-to-weight ratio and corrosion resistance, thus can be used to replace the steel plates in the BSP retrofitting system. This experimental study aims to investigate the flexural capacity of BSP beams with aluminum plates. The flexural strength, stiffness, and ductility of seven specimens with different plate thickness, plate height, bolts spacing, anchoring techniques, and prestressing were investigated. Compared with the reference RC beam, increasing the thickness of aluminum plates and reducing the spacing of bolts increased the bearing capacity and secant stiffness by 56% ∼ 66% and 33% ∼ 37%, and decreased the relative slips between aluminum plates and concrete, diminished the buckling in the compressive region of aluminum plates. Compared to bolt connection, using adhesive bonding to anchor aluminum plates yielded an improved cooperative effect between the aluminum plates and RC beam before the invalidation of adhesive bonding. The implementation of prestressing to aluminum plates before bolt-anchoring could recover the RC beam's flexural deflection under sustained load for about 60%. An analytical model was also proposed to calculate the flexural capacity of BSP beams with aluminum plates. And the theoretical and experimental results were found to be consistent with an average error of 9.6%.